Peran Komunikasi Orang Tua Dalam Menjaga Kesehatan Mental Remaja Di SMA N 11 Kota Medan - Ainul Mardiyah; Nana Gita Utami; Dewi Maryama. H. Rangkuti; Muhammad Alvin Tajir Sudiro (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Adolescent mental health is a crucial aspect of psychosocial development, influenced by the quality of communication between parents and children. This study aims to analyze the role of parental communication in maintaining adolescent mental health at SMA Negeri 11 Medan. The study used a qualitative approach using in-depth interviews with several adolescents as key informants. The interview instrument covered the frequency of communication with parents, emotional experiences after interactions, expected forms of support, and adolescents' perspectives on the role of communication in maintaining mental health. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that open, empathetic, and supportive communication from parents can increase adolescents' sense of emotional security, strengthen emotional regulation, and foster psychological resilience. Conversely, minimal or authoritarian communication patterns can cause emotional distress and diminish mental well-being. This study confirms that effective communication within the family is a protective factor for adolescent mental health in the school environment.